The Effect of the Implementation of Standard Operating Procedures (SOP) Code of Ethics and Work Discipline on the Performance of Employees of the Talaga Jaya Health Center in Talaga Jaya Regency - Nadia Nazwa Mohamad; Herlina Jusuf; Yasir Mokodompis (Universitas Muhammadiyah Palu, 2025)
The implementation of SOPs, codes of ethics and work discipline is a problem that needs to be considered in order to create good service and ethical standards as well as professionalism among medical and non-medical staff. The formulation of the problem is whether the application of operational standards, procedures, codes of ethics and work discipline affects the performance of employees of the Talaga Jaya health center, Gorontalo Regency. The purpose of the research was to determine the effect of the implementation of operational standards, procedures, code of ethics and work discipline on the performance of employees of the Talaga Jaya Health Center, Gorontalo Regency. Quantitative research design uses Analytic survey with Cross Sectional approach design. Sampling uses total sampling. The population in this study is all permanent employees who are actively working at the Talaga Jaya Health Center in 2024 totaling 54 people. The results of this study show that the standard variable of the code of ethics procedure was obtained with a value of 8,247 with a significance value of 0.00 < 0.05 where the value of t shows that there is a significant influence of the standard operating procedure variable on the performance of the work discipline variable has a value of 25.769 with a t level of 0.01 indicating that the discipline variable has a significant influence on the performance variable. It is recommended that the Talaga Jaya Health Center further improve the supervision and evaluation system. For the next researcher, it is recommended to research other variables related to employee performance